KAIDAH BELAJAR MATEMATIKA DALAM MEMBENTUK KARAKTER SISWA SEKOLAH DASAR - Karlimah karlimah (Al-Aulad: Journal of Islamic Primary Education, 2018)
Practically mathematical learning is often carried out through the provision of learning facilities to achieve the goal of skillfully solving the problem. Probably, quite a lot of mathematics learning is done through the provision of learning experiences to find rules or formulas. However, there is not much mathematics learning that provides the learning experience of mathematics along with the values of the learning mathematics developed in each student. In general, this paper writes about what and how to learn maths of value, so as to characterize. In particular, this paper writes about the notion of learning mathematics, characters, and learning mathematics that develop character. This article is to be understood and acted upon by teachers, student prospective teachers, parents, and the general public in increasing knowledge and stimulus in developing the willingness and learning ability and teaching students/children about mathematics.